2019
DOI: 10.1001/jamanetworkopen.2019.0088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal Docosahexaenoic Acid Supplementation on Blood Pressure in Children With Overweight Condition or Obesity

Abstract: Key Points Question Is maternal intake of prenatal docosahexaenoic acid associated with reductions in childhood blood pressure? Findings In this prespecified secondary analysis of a randomized clinical trial and follow-up of 171 mothers and their offspring, the children of women randomized to receive prenatal docosahexaenoic acid did not experience an increase in systolic blood pressure and diastolic blood pressure if they became overweight or obese compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…While the trials are too different in their manipulation and in their fundamental sample demographics to compare directly here, they do share a fair number of harmonized outcome variables in the domain of postnatal cognitive development to invite a putative inference that postnatal supplementation might produce more pervasive long-term positive effects on infant child neurocognition [72] than prenatal supplementation. On the other hand, the prenatal supplementation produced clear metabolic effects [73] that were not evident from the postnatal trial. While these outcomes and comparisons cannot be considered definitive, they do invite a vision of what might be possible with broadly harmonized outcomes for clinical trials in the future in the field of nutrition.…”
Section: Age and Timing In Nutritional Studiesmentioning
confidence: 88%
“…While the trials are too different in their manipulation and in their fundamental sample demographics to compare directly here, they do share a fair number of harmonized outcome variables in the domain of postnatal cognitive development to invite a putative inference that postnatal supplementation might produce more pervasive long-term positive effects on infant child neurocognition [72] than prenatal supplementation. On the other hand, the prenatal supplementation produced clear metabolic effects [73] that were not evident from the postnatal trial. While these outcomes and comparisons cannot be considered definitive, they do invite a vision of what might be possible with broadly harmonized outcomes for clinical trials in the future in the field of nutrition.…”
Section: Age and Timing In Nutritional Studiesmentioning
confidence: 88%
“…As child's height and child's BMI could be an intermediate or modifying factor in the association between DHA and BP, given evidence in the literature on an association between DHA and height [40,41] and DHA and BP in overweight children [42], we performed a sensitivity analysis where we used height and BMI as the outcome instead of BP. For those studies that had an intervention component by design (related or unrelated), we checked whether the associations were similar for the intervention and control arms.…”
Section: Discussionmentioning
confidence: 99%
“…The few n-3 LC-PUFA programming studies performed in animal models (as reviewed in Muhlhausler et al, 2011) support the notion that n-3 LC-PUFA may ameliorate unfavorable metabolic outcome due to an adverse perinatal environment, i.e. fetal dexamethasone exposure or neonatal overfeeding (Wyrwoll et al, 2006;Hou et al, 2012;Hidaka et al, 2018;Kerling et al, 2019). Indeed, we recently showed that an early diet containing large, PL coated lipids droplets (Nuturis ® , Gallier et al, 2015) in early life improved long term metabolic outcomes in growth restricted rats when challenged with a western style diet later in life (Teller et al, 2018).…”
Section: Critical Periods In Mice and Menmentioning
confidence: 97%